2022
DOI: 10.3390/cancers14235934
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Inflammatory Biomarkers as Prognostic Indicator in Salivary Gland Malignancy

Abstract: Background: The aim of this study was to investigate how the systemic inflammation response index (SIRI), systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), taken individually and combined, are associated with overall survival (OS) in patients surgically treated for malignant salivary gland tumors (MSGTs). Methods: A retrospective analysis of 74 cases following surgery at our department between January 2011 and June 2018 was performed. The Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…For example, pre-treatment neutrophil-to-lymphocyte ratio (NLR) has been investigated, and a strong statistical correlation was observed with positive neck occult metastasis in laryngeal squamous cell carcinoma [35]. Another study by Orabona et al confirmed the independent prognostic power of the systemic immune-inflammation index (SII) and the systemic inflammation response index (SIRI) on OS of patients who received malignant salivary gland tumor surgery [36].…”
Section: Discussionmentioning
confidence: 98%
“…For example, pre-treatment neutrophil-to-lymphocyte ratio (NLR) has been investigated, and a strong statistical correlation was observed with positive neck occult metastasis in laryngeal squamous cell carcinoma [35]. Another study by Orabona et al confirmed the independent prognostic power of the systemic immune-inflammation index (SII) and the systemic inflammation response index (SIRI) on OS of patients who received malignant salivary gland tumor surgery [36].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the combination of these biomarkers, particularly the SII and SIRI scores, has been evaluated as useful in preoperative risk stratification to effectively guide the treatment strategy and postoperative follow-up of patients with salivary gland malignancies. This combination, consolidating all three parameters simultaneously in the formula, has the capacity to fully assess the balance between the host immune and inflammatory conditions [ 17 ]. Inflammatory biomarkers, in addition to playing a supportive role in the assessment of poor prognosis, can also be used as diagnostic tools in difficult cases to provide proper guidance for the treatment of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recently, blood inflammatory indices have also been recognized as prognostic indicators for MSGTs. Abbate et al 13 have demonstrated that the combination of SII + SIRI is a valid, fast, and low-cost prognostic system to stratify patients at a higher risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%